Does asking learners to revise add to the effect of written corrective feedback on L2 acquisition?. (November 2020) - Ekanayaka, Waruni Iresha; Ellis, Rod
Abstract: The study investigates the add-on effect of asking students to revise following written corrective feedback. 91 students in three intact classes in a university in Sri Lanka completed three problem-solution writing tasks over a four-week period. One group revised their writing, with half keeping their corrections when writing a new task and the other half not having access to them. A second group completed the new tasks after discussing the feedback in pairs but without revising. A third group completed the tasks without feedback or the opportunity to revise. Results showed that the two groups that received feedback made greater gains in accuracy in finite verb constructions from the first to the second task than the control group. The group that had the opportunity to revise before completing a new writing task made the greatest gains. A stronger add-on effect for revising was evident in those learners who kept the corrected first draft when writing a new task. However, the effects of all the corrective treatments disappeared on the third more difficult task. The results are discussed in terms of the contribution that revision following feedback can make to improving grammatical accuracy in new writing.